<span>Y(−3, 4) is the original
</span><span>(x, y) → (x − 2, y + 1) is the rule you're using
(-3, 4) </span>→ (-3 - 2, 4 + 1)
(-3, 4) → (-5, 5)
<span>Y'(–5, 5)</span>
Answer:
2. the sum of 2 terms
Step-by-step explanation:
It is the sum of 2 terms because in this expression you are simply just adding.
Answer:
C is the answer i
Step-by-step explanation:
Answer:
NO
Step-by-step explanation:
In order to find the inverse you switch the x and y and solve for y.
x=(3/y )+3
x-3=3/y
y(x-3)=3
y= 3/x-3
no that doesn't equal h(x)